Book reviews - Hanne Trautner-Kromann; Albert van der Heide; Eva-Maria Jansson; Martin Schwarz Lausten (Nordisk Judaistik, 1999)
To come to the Land. Immigration and settlement in 16th-century Eretz-Israel (Abraham David, 1999) is reviewed by Hanne Trautner-Kromann.In Zion and Jerusalem. The itinerary of rabbi Moses Basola (1521–1523) (ed. Abraham David, 1999) is reviewed by Hanne Trautner-Kromann.The Jews in Palestine in the eighteenth century. Under the patronage of the Istanbul committee of officials for Palestine (Jacob Barnai, 1992) is reviewed by Hanne Trautner-Kromann.The message of a Mitsvah. The Mezuzah in rabbinic literature (Eva-Maria Jansson, 1999) is reviewed by Albert van der Heide.The Jewish-Christian controversy from the earliest times to 1789, Volume I, History (Samuel Krauss, 1996) is reviewed by Hanne Trautner-Kromann.Landet och missionen. Två studier över aktuella israeliska teman (Rune Lindblom & Malin Lindblom, 1999) is reviewed by Eva-Maria Jansson."Mit Zaum und Zügel muss man ihr ungestüm Bändigen" Ps. 32,9. Ein Beitrag zur christlichen Hebraistik und antijüdischen Polemik im Mittelalter (Ursula Ragacs, 1997) is reviewed by Martin Schwarz Lausten.